2022
DOI: 10.3802/jgo.2022.33.e54
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life outcomes from the randomized trial of hyperthermic intraperitoneal chemotherapy following cytoreductive surgery for primary ovarian cancer (KOV-HIPEC-01)

Abstract: Objective To investigate the health-related quality of life (HRQOL) related to hyperthermic intraperitoneal chemotherapy (HIPEC) following primary or interval cytoreductive surgery for primary ovarian cancer. Methods Between 2010 and 2016, a total of 184 patients were randomly assigned to receive cytoreductive surgery with HIPEC (n=92) or without HIPEC (n=92). Quality of life (QOL) assessment was evaluated at baseline (before surgery); on postoperative day 7; after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Conventional intravenous chemotherapy is ineffective in killing and removing residual lesions and free tumor cells, which is associated with an increased risk of ovarian cancer recurrence [ 16 ]. HIPEC is a new type of chemotherapy based on the different tolerance of tumor cells and normal cells to temperature, and HIPEC causes irreversible damage to tumor cells at 43°C [ 17 ]. The HIPEC technique improves the activity of chemotherapeutic drugs, promotes the intertissue penetration of drugs, and interferes with the metabolism of tumor cells, which well inhibits ovarian cancer cells from developing distant metastases [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional intravenous chemotherapy is ineffective in killing and removing residual lesions and free tumor cells, which is associated with an increased risk of ovarian cancer recurrence [ 16 ]. HIPEC is a new type of chemotherapy based on the different tolerance of tumor cells and normal cells to temperature, and HIPEC causes irreversible damage to tumor cells at 43°C [ 17 ]. The HIPEC technique improves the activity of chemotherapeutic drugs, promotes the intertissue penetration of drugs, and interferes with the metabolism of tumor cells, which well inhibits ovarian cancer cells from developing distant metastases [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several existing RCT studies, significant difference in adverse effects was not observed in the HIPEC and control groups [ 13 15 ]. Moreover, HIPEC does not appear to reduce health-related quality of life of patients, as shown in the KOV-HIPEC-01 study [ 29 ]. However, in another study, a significant increase in hypoalbuminemia, nausea, vomiting, and electrolyte disturbance was reported in the HIPEC group [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term quality of life in CRS/HIPEC patients has been a subject of debate. Several studies have demonstrated that the majority of patients return to baseline within one year of CRS/HIPEC [ 14 , 15 ]. The addition of HIPEC to CRS alone has also been shown to be safe [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%